Comparison on biomass production of three fodder germplasms (Bangladesh Journal of Animal Science, 2013)
The experiment was conducted to study the comparison on biomass production of fodder germplasm. Para (Brachiaria mutica Stapf.), German (Echinochloa crusgalli L.) and Dhal (Hymenachne pseudointerrupta C. Muell) grasses were cultivated in a completely randomized design (CRD). The whole area was divided into nine plots. The area of each unit plot was 6 m x 6 m. Number of cuttings were 16,000 /hectare where Plant to Plant distance was 16 cm and row and raw distance was 16 cm. Equal amount of organic and chemical fertilizer were applied in all cutting. The fodders were first harvested after 60 days of planting, second and third after successive 60 days of re-growth. The findings of the study showed that fresh biomass (p